Approximation of functions from the classes $W_{β}^r H^{α }$ by Weierstrass integrals - Hrabova, U. Z.; Kalchuk, I. V.; Stepanyuk, T. A. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We investigate the asymptotic behavior of the least upper bounds of the approximations of functions from the classes$W_{β}^r H^{α }$ by Weierstrass integrals in the uniform metric.